2003
DOI: 10.1128/iai.71.2.891-903.2003
|View full text |Cite
|
Sign up to set email alerts
|

Phagocytosis and Intracellular Fate ofAspergillus fumigatusConidia in Alveolar Macrophages

Abstract: Aspergillus fumigatus is the most prevalent airborne fungal pathogen responsible for fatal invasive aspergillosis in immunocompromised patients. Upon arrival in the lung alveolus, conidia of A. fumigatus are phagocytosed by alveolar macrophages, the major phagocytic cells of the lung. Engulfment and intracellular trafficking of A. fumigatus conidia in alveolar macrophages of two different origins, the murine cell line MH-S and human pulmonary alveolar macrophages, were analyzed by electron microscopy and immun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
228
1
5

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 248 publications
(242 citation statements)
references
References 77 publications
8
228
1
5
Order By: Relevance
“…Aspergillus spores (resting conidia) are ubiquitous in the environment, are inhaled frequently, and are normally cleared without pathology in immunocompetent people. Alveolar macrophages constitute a primary line of innate cellular defense, because they bind, ingest, and kill conidia (2,3). Organisms that escape macrophage killing are able to mature into germ tubes and hyphae, which can invade vessels and disseminate hematogenously; invasive pneumonia and disseminated infection is particularly common in people who lack effective hyphal defense by polymorphonuclear phagocytes (2).…”
Section: P Ulmonary Infections Caused Bymentioning
confidence: 99%
“…Aspergillus spores (resting conidia) are ubiquitous in the environment, are inhaled frequently, and are normally cleared without pathology in immunocompetent people. Alveolar macrophages constitute a primary line of innate cellular defense, because they bind, ingest, and kill conidia (2,3). Organisms that escape macrophage killing are able to mature into germ tubes and hyphae, which can invade vessels and disseminate hematogenously; invasive pneumonia and disseminated infection is particularly common in people who lack effective hyphal defense by polymorphonuclear phagocytes (2).…”
Section: P Ulmonary Infections Caused Bymentioning
confidence: 99%
“…Unbound conidia were removed by washing with cold RPMI complete medium, and phagocytosis was initiated at 37°C in an atmosphere of 5% CO 2 . Phagocytosis was stopped after 2 h by washing the AMs with ice-cold PBS and subjecting them to fixation with 3% formaldehyde in PBS (10 min at room temperature) followed by three washes with 50 mM NH 4 Cl in PBS. The number of A. fumigatus conidia engulfed by macrophages was determined using a polyclonal anti-conidia Ab and a secondary Ab conjugated to Texas Red.…”
Section: Phagocytosis Assaymentioning
confidence: 99%
“…Phagocytosis assays were performed as previously described (4). AMs were challenged with two conidia per macrophage and were subsequently incubated at 4°C for 30 min.…”
Section: Phagocytosis Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…Previous in vivo and in vitro studies have demonstrated that endothelial cells can adhere or endocytose the Aspergillus fumigatus spores, resulting in increased expression of the inflammatory factors interleukin (IL)-1, tumor necrosis factor (TNF)-α, IL-6 and IL-8 (3)(4)(5). In vascular endothelial cells, the receptor that recognizes the Aspergillus fumigatus fungus is not clear to date.…”
Section: Introductionmentioning
confidence: 98%